Preparing research articles - Thyer, Bruce A. (Oxford : Oxford University Press, 2008)
Thyer's frank advice on selecting an appropriate journal, handling rejections and revisions, understanding confusing concepts like impact factors and electronic publishing, and avoiding common methodological and formatting pitfalls, constitute a goldmine for the fledging researcher-writer.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sociology -- Authorship -- Handbooks, manuals, etc; Sociology -- Research -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc